Analysis of Elastohydrodynamic Lubrication for Steel-polymer Spur Gear Pairs - Zhou Jia'ao; Liu Xiaoling; Li Qun; Zhang Zheng (Jixie chuandong)
Polymer gears have the advantages of good self-lubrication and low production cost. Polymer gears are susceptible to pitting failure in transmission due to load, lubrication, etc. Metal-polymer gears' pairs have a longer service life than polymer-polymer gear pairs. To investigate the performance of elastohydrodynamic lubrication for metal-polymer gear pairs under lubrication condition, analysis of elastohydrodynamic lubrication is carried out for steel-polymer gear pairs under different working conditions, and the lubrication status and micro-pitting failure are determined by film thickness ratios and oil film safety factors. The results show that steel-polyoxymethylene (POM) gears' pairs can form stable lubricant film under oil lubrication, and the pressure angle, the rotational speed, the load and the viscosity can affect the lubrication state of gears. Therefore, the effects of pressure angle, rotational speed, load and lubricant viscosity need to be considered to avoid pitting failure.